2017
DOI: 10.1177/0269881117695879
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic treatment of schizotypy and schizotypal personality disorder: a systematic review

Abstract: Schizotypal personality disorder (SPD) is characterised by thought disorders, experiences of illusions, obsessive ruminations, bizarre or eccentric behaviour, cognitive problems and deficits in social functioning - symptoms that SPD shares with schizophrenia. Efforts have been undertaken to investigate the relationship between these conditions regarding genetics, pathophysiology, and phenomenology. However, treatment of SPD with antipsychotics has received less scientific attention. Embase and PubMed databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Antipsychotics also treat manic episodes 280 . Moreover, emerging evidence suggests that antipsychotics can reduce psychoticism in patients who do not have frank psychosis 281 . However, antipsychotics are much less efficacious for the detachment spectrum, such as for negative symptoms, and observed benefits may be limited to secondary negative symptoms 282 .…”
Section: Validity Evidencementioning
confidence: 99%
“…Antipsychotics also treat manic episodes 280 . Moreover, emerging evidence suggests that antipsychotics can reduce psychoticism in patients who do not have frank psychosis 281 . However, antipsychotics are much less efficacious for the detachment spectrum, such as for negative symptoms, and observed benefits may be limited to secondary negative symptoms 282 .…”
Section: Validity Evidencementioning
confidence: 99%
“…A recent systematic review has reported very few eligible studies (randomized control trials, cohort studies, retrospective non‐analytical studies and case studies) on treatment evaluation: 22 studies of the effects of pharmacological treatment and only three on psychotherapy . The studies examining pharmaceutical interventions found low to moderate evidences of the benefit of second‐generation antipsychotics, with most work focusing on risperidone . Among the studies of psychotherapy for SPD, one was a randomized clinical trial (RCT) comparing a form of integrated multifamily psychotherapy (psychoeducation, assertive and social skills training) with treatment as usual; in this study, the integrated therapy arm was less likely to transition to psychosis when compared with treatment as usual.…”
Section: Introductionmentioning
confidence: 99%
“…Higher degrees of both positive and negative schizotypy have also been correlated with difficulties forming complex and integrated ideas of the self and other and the ability to use that knowledge to respond to psychosocial stressors in a community sample . Schizotypy has been suggested as representing a latent organized set of personality traits, which may be present in a variety of schizophrenia‐related phenotypes, as well as a set of maladaptive traits found among persons in general, which may collapse into a full‐blown PD at the pathological end along the continuum of schizotypy …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations